Revision of the ‘dragon-head’ cusk eels of the genus Porogadus (Teleostei: Ophidiidae), with description of eight new species and one new genus - Schwarzhans, Werner W.; Møller, Peter R. (Zootaxa, 2021)
The ophidiid genus Porogadus occurs between 800 and 5300 m in the tropical and subtropical world oceans. Fifteen nominal species have been described since 1878 and most of them until 1902. The genus has been highlighted as needing revision in recent compilations about ophidiiforms and here we present the first comprehensive review. Twelve of the previously described species are here accepted as valid with two being moved to the newly established genus Tenuicephalus n. gen. that encompasses fishes differing from those of Porogadus in the extremely weak ossification, the stout head, absence of head spines and absence of the “triple” lateral line system considered typical for Porogadus and a reduced dentition. In addition, eight new species are described: Porogadus caboverdensis, P. dracocephalus, P. lacrimatus, P. mendax, P. solomonensis, P. turgidus, Tenuicephalus multitrabs and T. squamilabrus.                The species of Porogadus show a distinctive depth segregation with the majority of species having a demersal bathyal life-style between 800 and 3500 m and other species being more or less exclusively restricted to abyssal depths below 3000 m. The biogeographic distribution pattern of bathyal groups shows putative species pairs in the Atlantic versus the eastern Pacific and a clear separation of eastern Pacific from Indo-West Pacific species. The geographic effects and timing are being discussed that may have led to this speciation events. Generally, we found widely distributed species that are found far away from continental masses and others restrained to continental slopes and sometimes exhibiting regionalism. In abyssal depth, the Cabo Verde and Canary basins off NW-Africa have yielded three exclusive species, but it is uncertain at this stage whether this could represent a sampling bias with this area being extensively sampled by the Discovery research vessel (BMNH) over the years from 1970–1998. Another instance of a potentially endemic abyssal species is that of Porogadus melanocephalus in the Bay of Bengal. The latter has been caught with 45 specimens in a single trawl, representing the highest number of Porogadus specimens collected in any trawl and indicating that these fishes may actually not be as rare as one might assume from the literature.